Using theory of change in child health service interventions: a scoping review protocol - Jones, B; Nagraj, S; English, M (F1000Research, 2022)
Background: The objective of this scoping review is to map the evidence of how child health service interventions use their theory of change. A theory of change is a hypothesis of how and why an intervention is intended to bring about change. It can be used as a program design, implementation, and evaluation tool. This scoping review will provide an overview of the evidence base for, and identify the way in which, theories of change in child health service interventions are defined, rationalised, developed, presented, and refined. Methods: The inclusion criteria for this scoping review is any child health service intervention globally, that describes their theory of change or theory of change development process. Relevant exclusions include: logic models or logic frameworks that do not meet this review’s definition of theory of change, systematic reviews, behavioural change interventions that target patient’s behaviour, school-based interventions, and maternal health interventions not related to child health outcomes. This scoping review will follow the Joanna Briggs Institute Reviewer’s manual. Relevant publications will be first searched on selected electronic databases and grey literature. A search strategy will be developed. The search will be limited to articles written in the English language. Results of the search will be curated using Endnote and duplicates removed. Results will be imported to Rayyan. The inclusion criteria will be applied during the process of title and abstract screening, by two independent reviewers and disagreements resolved by a third independent reviewer. Full-texts will have the inclusion criteria applied via the same reviewer process. Data relevant to the research sub-questions will be extracted, analysed, charted and discussed. Ethics and dissemination: Ethical approval is not required for this review as we will make use of already published data. We aim to publish the findings of our review in a peer-reviewed journal.